Genome-wide identification, expression profile and selection analysis of the CPK gene family in Nelumbo nucifera - Teng Cheng; Mengyang Li; Chufeng Zhao; Tao Wang; Xingwen Zheng; Liangbo Yang; Ying Diao; Sai Yang; Zhongli Hu (BMC Genomics)
Abstract Background Lotus (Nelumbo nucifera Gaertn.) is an ancient relic plant that has applications as an aquatic flower, herbal medicine, and vegetable. It is responsive to environmental stress. Calcium functions as a ubiquitous second messenger in various signal transduction pathways in plants. Calcium-dependent protein kinases (CPKs), which are serine/threonine-protein kinases commonly found in plants, have significant impacts on plant growth, development, and resilience to adversity. However, the genes encoding calcium-dependent protein kinases (CPKs) in lotus remain unclear. Results In this study, the CPK gene family was systematically and comprehensively identified and analyzed. The 27 CPKs of lotus were further categorized into five subfamilies based on gene structure and phylogenetic tree analysis. Segmental duplication was found to be the primary event of CPK gene duplication, and all identified CPK genes underwent purifying selection. Comparative genomics analysis between lotus and model or non-model plants revealed that a large number of ancient CPKs were retained in lotus. Additionally, several distinct CPKs with strong elimination signals were selected from different ecotypes and cultivation types. The expression of CPKs was tissue-specific and regulated under abiotic stress. Therefore, it is suggested that CPK may confer potential advantages in some biological adaptations of lotus during long-term survival and artificial domestication. Overall, this research not only elucidates the relationship between CPK gene evolution and function among species but also lays a valuable foundation for future molecular breeding research on the function of CPK in lotus. Conclusion This study represents the first comprehensive investigation of lotus CPK genes at a genome-wide level, revealing their uneven distribution among eight chromosomes. The NnCPKs were categorized into five groups, and an in-depth analysis of their structure and organization was conducted. By comparing genomes, we gained a better understanding of gene functions based on their homologs. Furthermore, the expression profiles in different tissues and responses to abiotic stresses indicated that these genes may play significant roles in lotus growth and development. These findings provide a valuable foundation for future functional studies of lotus CPK genes to explore their biological effects.